Archeology, architecture and art in Caqui, province of Huaral - Alvino Loli, Jorge (2016)
The present work is a synthesis of the investigations carried out in the lower valley of the Chancay river, focused on recognizing, recording and analyzing the cultural expressions materialized in the historical buildings existing in the vicinity of Caqui, former hacienda house of the district of Aucallama in the province of Huaral, department of Lima. The interest is in contextualizing the aesthetic works incorporated in architecture, perceiving them in relation to their spatial geographical environment, as well as the social processes in which they were inserted temporarily, in order to understand their social meaning. In this sense, two types of expression of different contexts are exposed: the mural representations of the Chancay society in ancient Peru, and the murals associated with the ‘haciendas’ system of the beginning of the Republic.